Family : natural habitat of the human being - basic structure of a true human ecology - Oviedo Valencia, Karin Anell (2018)
We understand as "natural habitat" the environmental or space that has the minimum physical and biological conditions required for the survival of a specie. If a particular habitat is altered or compromised by any external or internal agent, the specie that inhabits could be in risk of extinction. Like all species on our planet, humans, also has the need for adequate natural ecological habitat, which allows them to live according to their human condition and reach their maximum development holistically. In this sense, the family plays a key role in the life of every individual, is in the family where the man learns to be a "person", and learn to love and value themselves and their fellows. The family is the first place that serves the man as a refuge, where you feel protected, loved, respected and accepted, regardless of their achievements or failures. According to the statement, the purpose of this paper is to highlight the importance of the family as the natural habitat of the human being and the necessity for its preservation and conservation, due the key role of the family in the formation of human being, also reinforce the concept of family as the basic structure of a true human ecology.